Efficacy and safety of picosecond 755‐nm alexandrite laser with diffractive lens array for non‐ablative rejuvenation in Chinese skin. Issue 1 (28th August 2018) - Wat, Heidi; Yee‐nam Shek, Samantha; Yeung, Chi Keung; Chan, Henry Hin‐lee
Abstract : Background and Objectives: The picosecond alexandrite laser with diffractive lens array (DLA) offers the dual advantages of a picosecond pulse duration and the fractionated delivery of laser energy. This study explores the efficacy and safety of the DLA for treatment of multiple aesthetic concerns associated with photoaging of the face including skin texture irregularities, dyspigmentation, enlarged pore size, rhytides, and skin laxity. Methods: This prospective, evaluator‐blinded trial enrolled Fitzpatrick skin type III–IV patients with mild to moderate signs of facial photoaging. Patients received six full face treatments at 4 week intervals for a total of 107 treatments. Standardized photography was obtained at baseline and at 1, 2, and 3 month follow‐up visits. Two independent blinded evaluators rated each of the five signs of photoaging on a 10‐point visual analog scale (VAS) at each follow‐up visit compared to baseline. A global aesthetic improvement score was also assigned at each follow‐up visit. Secondary outcomes included patient‐rated pain and heat sensation on a 10‐point VAS, and overall satisfaction. Adverse events were noted after each treatment and at each follow‐up visit. Results: A total of 18 Chinese patients age 35–59 completed the study. A statistically significant improvement in skin texture and dyspigmentation scores was noted at the 1 month follow‐up that was sustained at 3 months. No significant improvements were observed in pore size, rhytides, or skin laxity. The mean pain score was 5.1 ± 2 and mean heat sensation was 3.6 ± 2.1. Expected transient erythema and edema occurred in 95.3% (102/107) and 1.9% (2/108) of treatments, respectively, and resolved in hours. No incidences of post‐inflammatory hyperpigmentation (PIH) were noted at the 1, 2, and 3 month visits. Conclusion: The 755‐nm picosecond laser with DLA is a safe and effective non‐ablative modality for targeting facial skin texture irregularities and dyspigmentation in Chinese skin. Patients tolerated the treatment well with adverse effects limited to transient erythema and edema. Lasers Surg. Med. 51:8–13, 2019. © 2018 Wiley Periodicals, Inc.